2022
DOI: 10.3390/ijms23158290
|View full text |Cite
|
Sign up to set email alerts
|

An Association between Insulin Resistance and Neurodegeneration in Zebrafish Larval Model (Danio rerio)

Abstract: Background: Type 2 diabetes mellitus has recently been identified as a mediator of neurodegeneration. However, the molecular mechanisms have not been clearly elucidated. We aimed to investigate insulin resistance associated with neurodegenerative events in zebrafish larvae. Methods: Larvae aged 72 h-post-fertilization (hpf) were induced to insulin resistance by immersion in 250 nM insulin and were then reinduced with 100 nM insulin at 96 hpf. This model was validated by a glucose levels assay, qPCR analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…Moreover, zebrafish larvae also developed an oxidative stress confirmed by the substantially high levels of the biomarker malondialdehyde (MDA), and the upregulation of MAPK and claudin‐5a genes. Altogether, these results confirm that the mechanisms of neurogeneration were altered and the blood–brain barrier further injured (Md Razip et al., 2022).…”
Section: Zebrafish Models For Diabetes and Diabetic Pathologiessupporting
confidence: 78%
“…Moreover, zebrafish larvae also developed an oxidative stress confirmed by the substantially high levels of the biomarker malondialdehyde (MDA), and the upregulation of MAPK and claudin‐5a genes. Altogether, these results confirm that the mechanisms of neurogeneration were altered and the blood–brain barrier further injured (Md Razip et al., 2022).…”
Section: Zebrafish Models For Diabetes and Diabetic Pathologiessupporting
confidence: 78%
“…Previous research has demonstrated that the constitutively active pdx1 can effectively induce insulin production (Imai et al., 2005). When zebrafish larvae were exposed to excessive insulin resulting in insulin resistance, the size of their yolk sac increased significantly, suggesting reduced yolk consumption (Md Razip et al., 2022). Interestingly, in cavefish, insulin resistance aids in adaptation to a nutrient‐limited environment (Riddle et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dorsemans et al (32) found that acute and chronic hyperglycemia impaired the regeneration and de novo formation of zebrafish neuronal cells, resulting to adverse effects on neurogenesis and brain healing. Alteration in the metabolic physiology associated with neurodegeneration was also found in the insulin resistance zebrafish larvae model by Razip et al (33). To evaluate the prevention of E70 on diabetic complication, the protective effect of PRA on peripheral nerve was evaluated by detecting the fluorescence intensity of peripheral motor nerve of normal and hyperglycemic zebrafish.…”
Section: Protective Effect Of Peripheral Motor Nervementioning
confidence: 94%